Registration of 'CP 12‐1417' sugarcane for organic soils in Florida. Issue 1 (7th December 2021) - Sandhu, H. S.; Zhao, D.; Davidson, R. W.; Gordon, V. S.; Islam, M. S.; McCord, P. H.; Sood, S.; Baltazar, M.; Arbelo, O. Coto; Momotaz, A.
Abstract: 'CP 12‐1417' (Reg. no. CV‐203, PI 698897) sugarcane (a complex hybrid of Saccharum spp.) was released in June 2019 for commercial cultivation on organic soil (Histosols) in Florida. CP 12‐1417 was developed through collaborative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugar Cane League, and it was released commercially by the Florida Sugarcane Variety Committee in June 2019. CP12‐1417 is the result of a cross CPX 09‐0511 made between CP 02‐2065 (female parent) and a collection of pollen donors (a polycross). Higher cane and sugar yields than the reference checks ('CP 96‐1252' with highest acreage in Florida and 'CP 00‐1101' with high sucrose concentration) in organic soil and complete or partial resistance to several important sugarcane diseases in Florida made CP 12‐1417 an ideal candidate for commercial release. Cane yield in CP 12‐1417 was 17 and 27% higher than in CP 96‐1252 and CP 00‐1101, respectively. Similarly, sugar yield in CP 12‐1417 was 23 and 22% higher than in CP 96‐1252 and CP 00‐1101, respectively. Economic index in CP 12‐1417 was 35 and 19% higher than in CP 96‐1252 and CP 00‐1101, respectively. Based on natural infestation and artificial inoculation disease data, CP 12‐1417 is resistant to brown rust (tested positive for Bru 1 marker), orange rust, leaf scald, and smut and moderately resistant to ratoon stunting disease, Sugarcane mosaic virus, and Sugarcane yellow leaf virus . CP 12‐1417 has poor freeze tolerance. Core Ideas: Sugarcane cultivar CP 12‐1417 was released for organic soil in Florida. CP 12‐1417 has higher cane and sugar yield than the reference checks. CP 12‐1417 is completely or partially resistant to economically important sugarcane diseases.